Teachers' Adaptability to General Curriculum Reform - Huyen, Nguyen Phuong; Yen, Duong Thi Hoang (VNU Journal of Science: Education Research, 2022)
The purpose of the research is to investigate the lecturers' adaptability  to curriculum innovation and its impact on the fundamental and comprehensive innovation of education and training. In order to adapt to curriculum reform, teachers must be prepared for their own role in curriculum design and implementation, aware of program changes and values. teaching in the direction of developing learners' capacity; skills to practice student-centered teaching strategies. The adaptation of teachers to curriculum innovation depends on the teachers themselves and the policy context of each school. Research methods are mixed methods combining qualitative and quantitative. Main data is from questionnaires provided to the trainers. Measures of data collection according to 3 aspects on the adaptability of lecturers to curriculum innovation. The results show that 651 respondents can adapt to a medium level, most of the lecturers are ready to adapt to the curriculum innovation. Some teachers have tried to actively self-study and develop professional competence.